Immune Checkpoint Marker of Programmed Death Ligand-1 (PD-L1) Expression in Surgical Lung Cancer Specimens - Elisna Syahruddin; Jamal Zaini; Lisnawati Lisnawati; Yayi DB Susanto; Sarah Fitriani; Shanty R. Kusumawardani; Romi Baginta (Jurnal Respirologi Indonesia, 2022)
Background: Currently immune checkpoint pathways of PD1-PD-L1 is being used to treat lung cancer and PD-L1 served as predictive biomarker. Investigations of PD-L1 expression as a target immunotherapy in lung cancer specimens in Indonesia is needed. This study aimed to evaluate PD-L1 expression in resected lung cancer specimens using immunohistochemistry techniques. Methods: Thirty surgically resected sample from lung cancer patients were obtained. The whole specimens were stained by using immunohistochemistry techniques automatically in BOND-MAX Autostainner (Leica, Germany). PD-L1 polyclonal antibody (Genetex) at 1:1500 dilution was applied to immunohistochemistry staining procedure. Clinicopathological characteristic were acquired from the hospital registry database.Result: A total of 30 surgical specimens were assessed from lung cancer patients. Twenty-four (80%) of them were Adenocarcinoma (AC), 1 (3, 33%) Adenosquamous carcinoma, 2 (6, 67%) were Squamous Cell Carcinoma (SSC), 1 (3, 33%) were Large Cell Carcinoma, 1 (3, 33%) were Neuroendocrine Carcinoma, 1 (3, 33%) were Adenoid Cyctic Carcinoma. The expression of PDL-1 positive reactivity was 16 of 30 (53.3%) specimens and we categorized into strong positivity (>50%), medium (= 50%) and low positivity (<50) from 21 specimens, 0 specimens and 7 specimens respectively.Conclusion: PD-L1 expression could be detected in lung cancer specimen using polyclonal antibody.